Preliminary Model for Environmental Management in the Production of Surfboards - Grijó, Paulo Eduardo Antunes (Journal of Environmental Accounting and Management, 2026)
The surfboard industry in Brazil and in the world has more than 50 years depositing toxic residues and flammablesin simple landfills without any control or environmental treatment. These residues, classified by the NBR 10004, as Class I, are considered hazardous, have high aggregated value and huge time decay. In the manufacturing process of this product, it has been identified the emerging need to perform an audit and to create an environmental management system for these units, aiming to reduce water consumption, electricity and wastes generation, apart from the recovery of the residues that cannot be eliminated. It was observed that industrial activity may be resized inorder to minimize environmental impacts and public health and also tomaximize financial resources. Since the year of 1999 researching alternatives for the recovery of residues generated in the production of surfboards, it was realized that this would be a core activity in a process of sustainability and with this; it was found the need of primarily working with the transformation of a culture of waste and consumerism, already established in this industry. For the construction of this initiative, it will benecessary to promote a system of education and of environmental awareness to the social-business level and make a diagnosis in a board factory, with the purpose of systematizing a reference model of ecological responsibility, leveraged through the promotion of forums of discussions and of formulation of a preliminary Environmental Management System for the surf industry.